Adipocyte and epidermal fatty acid-binding protein serum concentrations in patients with lipodystrophy. (April 2017) - Miehle, Konstanze; Ebert, Thomas; Kralisch, Susan; Hoffmann, Annett; Kratzsch, Jürgen; Schlögl, Haiko; Stumvoll, Michael; Fasshauer, Mathias
Highlights: AFABP and EFABP levels do not differ between lipodystrophy patients and controls. Serum AFABP and EFABP are not related to markers of glucose or lipid metabolism. AFABP serum concentration correlates with gender, serum leptin and BMI. Abstract: Objective: Lipodystrophy (LD) syndromes are associated with diabetes mellitus, hypertriglyceridemia, and coronary artery disease. One pathogenetic factor of LD is dysregulation of several adipokines. However, the insulin resistance- and dyslipidemia-promoting adipokines adipocyte (AFABP) and epidermal (EFABP) fatty acid-binding protein have not been investigated in non-HIV-associated LD so far. Material and methods: We performed a cross-sectional analysis of AFABP and EFABP serum concentrations in 37 LD patients and 37 age-, gender-, and body mass index-matched healthy controls. Moreover, AFABP and EFABP were correlated to clinical and biochemical parameters of inflammation, glucose control, and lipid metabolism. Results: There was no significant difference in median circulating AFABP and EFABP levels between LD patients (21.7 μg/l and 7.5 μg/l, respectively) and healthy controls (24.5 μg/l and 8.6 μg/l, respectively). Neither AFABP nor EFABP were related to markers of impaired glucose control or lipid metabolism. Multiple linear regression analysis showed a positive and independent association of AFABP with gender, serum leptin levels, and body mass index. Conclusions: Circulating levels of AFABP and EFABP are not decreased in LD despite adipose tissue loss in contrast to other adipokines including leptin and adiponectin.